Perception Analysis of Complexity, Computer Anxiety, and Self-Efficacy of the Village Treasurer towards the Use of the SISKEUDES Application - Wardhani, Aurelia Melinda Nisita; Ryantama, Nicolaas Aditya (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2019)
The SISKEUDES is used to help manage good and orderly village finance in village financial reporting. However, the implementation of this IS was not easy for the village treasurer to do because of knowledge limitation to manage the budget including village income and expenditure. This study aims to evaluate the perceptions of the village treasurer about the acceptance and use of the SISKEUDES. This research is a case study in Bantul district, Special Region of Yogyakarta, Indonesia. The survey was conducted through questionnaires and interviews. The sample in this study was 86 village treasurers who used the SISKEUDES. Smart Partial Least Square 3.2 software is used to test the hypothesis in this study. The results of this study indicate that the village treasurer has accepted and used the IS properly. Self-efficacy have a significant influence with perceived usefulness and perceived ease of use of the SISKEUDES. Meanwhile, complexity does not have a significant effect on perceived ease of use IS users. In addition, computer anxiety has no significant effect on the ease of using the SISKEUDES.